Phytoremediation of Toxic Metals: A Sustainable Green Solution for Clean Environment - S. M. Omar Faruque Babu (MDPI AG, 2021)
Contamination of aquatic ecosystems by various sources has become a major worry all over the world. Pollutants can enter the human body through the food chain from aquatic and soil habitats. These pollutants can cause various chronic diseases in humans and mortality if they collect in the body over an extended period. Although the phytoremediation technique cannot completely remove harmful materials, it is an environmentally benign, cost-effective, and natural process that has no negative effects on the environment. The main types of phytoremediation, their mechanisms, and strategies to raise the remediation rate and the use of genetically altered plants, phytoremediation plant prospects, economics, and usable plants are reviewed in this review. Several factors influence the phytoremediation process, including types of contaminants, pollutant characteristics, and plant species selection, climate considerations, flooding and aging, the effect of salt, soil parameters, and redox potential. Phytoremediation’s environmental and economic efficiency, use, and relevance are depicted in our work. Multiple recent breakthroughs in phytoremediation technologies are also mentioned in this review.